2017
DOI: 10.1111/cup.12934
|View full text |Cite
|
Sign up to set email alerts
|

Syringocystadenocarcinoma papilliferum: Clinicopathologic analysis of 10 cases

Abstract: Because of high rates of regional lymph node metastasis and mortality in our patients, clinical behavior of SCACP seems to be more aggressive than that previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 34 publications
1
44
0
Order By: Relevance
“…Other reported histopathologic findings in this adnexal adenocarcinoma include intraepidermal and intrafollicular pagetoid spread, so‐called “dirty necrosis”, mucinous ductal metaplasia and ductal changes analogous to those seen in the breast. A recent study supported that the biological behavior of syringocystadenocarcinoma papilliferum seems to be more aggressive than previously reported …”
Section: Introductionsupporting
confidence: 74%
“…Other reported histopathologic findings in this adnexal adenocarcinoma include intraepidermal and intrafollicular pagetoid spread, so‐called “dirty necrosis”, mucinous ductal metaplasia and ductal changes analogous to those seen in the breast. A recent study supported that the biological behavior of syringocystadenocarcinoma papilliferum seems to be more aggressive than previously reported …”
Section: Introductionsupporting
confidence: 74%
“…WLE has been the mainstay treatment for localized SCACP; however, high recurrence rate (30-40%) following surgery has been reported [ 4 , 6 ]. For unresectable or metastatic disease, no standard treatment has yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…The invaginations and papillary projections are lined by two-layer epithelium: the luminal layer composed of columnar cells with decapitation secretions and the outer layer composed of small cuboidal cells. The immunohistochemical features of SCACP are still under study, but the most frequently reported markers are CEA, 15,20,28 followed by EMA, 9,28 GDFP-15, 20,28,32 and cytokeratin. 11,28,32 Due to its appearance, the differential diagnosis includes other skin tumors such as basal cell carcinoma, squamous cell carcinoma, sebaceous carcinoma, metastatic breast or gastrointestinal adenocarcinomas, and other sweat gland neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemical features of SCACP are still under study, but the most frequently reported markers are CEA, 15,20,28 followed by EMA, 9,28 GDFP-15, 20,28,32 and cytokeratin. 11,28,32 Due to its appearance, the differential diagnosis includes other skin tumors such as basal cell carcinoma, squamous cell carcinoma, sebaceous carcinoma, metastatic breast or gastrointestinal adenocarcinomas, and other sweat gland neoplasms. 2,20 Of the cases that reported head and neck involvement, 16 (72.72%) were in remission following therapy, 2 (9.09%) had local recurrence, 3 (13.63%) had regional lymphatic invasion, and 1 (4.54%) had distant metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation